Respons Pertumbuhan Tanaman Terong (Solanum melongena L.) Terhadap Pemberian Unsur Hara Organik Limbah Kulit Pisang Kepok (Musa acuminata L.) - Ita Emilia; Dewi Novianti; Tesya Vinolasari; Parasmita Anggraini (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2022)
Research on Eggplant (Solanum melongena L.) Growth Responses to Application of Organic Nutrients from Kepok Banana Peel Waste (Musa acuminata L.), aims to examine the provision of appropriate nutrient concentrations for eggplant plant growth. This study used the RAL experimental method, namely the administration of banana peel organic nutrients consisting of 6 treatments and 4 replications, namely P0 (without nutrients), P1 (100 ml/L of nutrients), P2 (200 ml/L of nutrients), P3 (300 ml). /L nutrients), P4 (400ml/L nutrients) and P5 (500ml/L nutrients). The results showed that the growth response of eggplant (Solanum melongena L.) to the application of organic nutrients from kepok banana peel waste (Musa acuminata L.) in the P5 treatment gave the highest yield at an average plant height of 7.5 cm, number of leaves 5, 5 strands and a stem diameter of 0.38 cm while the lowest average value was found at P0 with an average plant height of 4.75 cm, number of leaves of 3.25 strands and a stem diameter of 0.27 cm.